Clinical and epidemiological characteristics of hepatocellular carcinoma cases in east and Southeastern region of Turkey: A multicenter retrospective study - Yalçin, Kendal; Yakut, Mustafa; De?ertekin, Halil; Türkdo?an, Kürşat; Harputluo?lu, Murat; Bahçecio?lu, Ibrahim Halil; Yilmaz, Nevin (Turkiye Klinikleri, 2013)
Objective: In this multicenter retrospective study, we aimed to investigate the epidemiological and clinical characteristics of patients with hepatocellular cancer (HCC) in the Eastern and Southeastern Anatolian regions of Turkey. Material and Methods: This study included 218 patients from 7 centers-Dicle University (n=96), Yüzüncü Yi{dotless}l University (n=30), İnönü University (n=28), Fi{dotless}rat University (n=24), Gaziantep University (n=20), Atatürk University (n=19), and Harran University (n=1) hospitals. Information about patients was obtained through pre-prepared forms. Diagnosis of HCC was made histologically or with a combination of clinical, radiological, and laboratory findings. Results: The mean age of the patients was 57.67±12.03 with a male-to-female ratio of 5.8:1. Etiologically, 45% of the study group had HBV infection alone, 29% had HDV co-infection, 15% had HCV infection and 10% were idiopathic cases with unknown etiology. Cirrhotic background was present in 94% of the patients and 89% of cases had an advanced stage disease according to the Okuda classification. Alpha-fetoprotein levels were over 300 ng/ml in 81% of the patients. Conclusion: Hepatitis B virus infection followed by hepatitis delta virus infections appeared to be the leading etiological factors for HCC cases in our region. HBsAg carriage continues to be an important risk factor for HCC in Turkey. The fact that most of the HCC cases are in the late stages of disease, makes it necessary to use effective diagnosis and treatment methods with efficient screening and monitoring programs in our country. © 2013 by Türkiye Klinikleri.
Türkiye'nin do?u ve güneydo?u bölgesinde hepatoselüler karsinomalı vakaların klinik ve epidemiyolojik özellikleri: Çok merkezli retrospektif çalışma
Keywords: Carcinoma; Epidemiology; Hepatitis B virus; Hepatitis delta virus; Hepatocellular